2015
DOI: 10.15390/eb.2015.2885
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Conceptions of Giftedness and Special Needs of Gifted Students

Abstract: Öz Anahtar KelimelerÖğretmenler, üstün zekâlı ve yetenekli öğrencilerin eğitiminde önemli bir role sahiptir. Etkili bir tanılama ve eğitim için, öğretmenlerin gelişmiş bir üstün zekâ kavramına ve üstün zekâlı ve yetenekli öğrencilerin özellikleri ve özel gereksinimleri hakkında kapsamlı bir bilgiye sahip olması gerekmektedir. Bu nitel araştırmada, Amerika Birleşik Devletleri'ndeki çeşitli devlet okullarında görev yapan on öğretmen ile görüşme yapılarak, onların sahip oldukları üstün zekâ kavramlarının ortaya ç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 29 publications
2
23
0
3
Order By: Relevance
“…Shaunessy (2005) emphasizes the students' emotional security in the classroom to enable them to function well in the learning process by responding to and asking higher-order questions or disclosing their opinions. However, a study in an American gifted education program revealed that teachers often find it difficult to deal with the individual gifted students because of their different needs and their never-ending questions (Kaya, 2015). This situation put them in a difficult situation, but they admitted that it is their responsibility to create suitable learning opportunities for these students and overcome the existing problems.…”
Section: Discussion and Conclusion Learning Climates At Schools And Tmentioning
confidence: 99%
“…Shaunessy (2005) emphasizes the students' emotional security in the classroom to enable them to function well in the learning process by responding to and asking higher-order questions or disclosing their opinions. However, a study in an American gifted education program revealed that teachers often find it difficult to deal with the individual gifted students because of their different needs and their never-ending questions (Kaya, 2015). This situation put them in a difficult situation, but they admitted that it is their responsibility to create suitable learning opportunities for these students and overcome the existing problems.…”
Section: Discussion and Conclusion Learning Climates At Schools And Tmentioning
confidence: 99%
“…Therefore, these conceptions play a significant role in helping young gifted students advance their talent (Mann, 2006;Pettersson, 2008). Several studies have shown that teachers relate giftedness to motivation to learn quickly, intelligently, and creatively (Kaya, 2015;Laine, Kuusisto, & Tirri, 2016;Mattsson, 2010;Moon & Brighton, 2008). One study of Swedish teachers saw motivation as including persistence and enjoyment of mathematics (Mattsson, 2010).…”
Section: Supporting the Motivation Of Gifted Studentsmentioning
confidence: 99%
“…It is interesting to note that Nordic teachers mainly associate positive socialemotional characteristics such as enthusiasm, sensitivity, and curiosity with giftedness (Kaya, 2015;Laine et al, 2016;Mattsson, 2010). In general, gifted students are seen as well-behaving, well-managing independent learners (Kaya, 2015;Mattsson, 2010;Moon & Brighton, 2008).…”
Section: Supporting Relationships Of Gifted Studentsmentioning
confidence: 99%
“…Respecto de los primeros, Al Zoubi (2018) encontró que algunas creencias se restringían a áreas académicas, mientras que otras incorporaban aspectos socioemocionales, como el desajuste social. Kaya (2015), constató que las creencias docentes pueden tener un fuerte impacto en términos de dónde focalizan su atención y a quienes consideran como potenciales candidatos a participar de programas para la atención de la AC.…”
Section: Alta Capacidadunclassified